A HISTORY OF THE WORLD'S RELIGIONS - DAVID S. NOSS (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2021)
"Detective Cate Reilly and former colleague Zeke Sloan-the man who once stole her heart-are reunited when she goes undercover at an exclusive girls' school and discovers that no one is who they seem to be . . . and danger waits at every turn"--
Keywords: Romantic suspense fiction